The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2010
DOI: 10.1182/blood-2010-01-265595
|View full text |Cite
|
Sign up to set email alerts
|

CD16− natural killer cells: enrichment in mucosal and secondary lymphoid tissues and altered function during chronic SIV infection

Abstract: Natural killer (NK) cells contribute to control of HIV/SIV infection. We defined macaque NK-cell subsets based on expression of CD56 and CD16 and found their distribution to be highly disparate. CD16 ؉ NK cells predominated in peripheral blood, whereas most mucosal NK cells were CD56 ؉ , and lymph nodes contained both CD56 ؉ and CD16 ؊ CD56 ؊ (doublenegative [DN]) subsets. Functional profiles were also distinct among subsets-CD16 ؉ NK cells expressed high levels of cytolytic molecules, and CD56 ؉ NK cells were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

33
193
0
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 105 publications
(227 citation statements)
references
References 51 publications
33
193
0
1
Order By: Relevance
“…In contrast, NKp44 ϩ NK cells expressed very little CD56 and were negative for CD16. Furthermore, NKp46 and CD8␣, 2 molecules often used to delineate NK cells in macaques, 5,29 were expressed at high levels on NKG2A ϩ NK cells but were dimly expressed on NKp44 ϩ NK cells ( Figure 1C). We also found greater levels of the chemokine receptor CCR6 on NKp44 ϩ NK cells compared with NKG2A ϩ NK cells, whereas CXCR3 was expressed at higher levels on NKG2A ϩ NK cells, similar to published reports for human NK cells.…”
Section: Siv Infection Alters Mucosal Nk-cell Function 3323mentioning
confidence: 99%
See 3 more Smart Citations
“…In contrast, NKp44 ϩ NK cells expressed very little CD56 and were negative for CD16. Furthermore, NKp46 and CD8␣, 2 molecules often used to delineate NK cells in macaques, 5,29 were expressed at high levels on NKG2A ϩ NK cells but were dimly expressed on NKp44 ϩ NK cells ( Figure 1C). We also found greater levels of the chemokine receptor CCR6 on NKp44 ϩ NK cells compared with NKG2A ϩ NK cells, whereas CXCR3 was expressed at higher levels on NKG2A ϩ NK cells, similar to published reports for human NK cells.…”
Section: Siv Infection Alters Mucosal Nk-cell Function 3323mentioning
confidence: 99%
“…Next, we further evaluated the functionality of NKG2A ϩ and NKp44 ϩ NK cells in a 4-function ICS assay adapted from previous assays optimized in our laboratory. 5 After mitogen stimulation, NKp44 ϩ NK cells secreted the regulatory cytokines IL-17 and TNF-␣ but little IFN-␥, and they expressed only low levels of the degranulation marker CD107a ( Figure 1F). In strong contrast, on stimulation NKG2A ϩ NK cells secreted no IL-17, significant amounts of IFN-␥, and up-regulated CD107a.…”
Section: Siv Infection Alters Mucosal Nk-cell Function 3323mentioning
confidence: 99%
See 2 more Smart Citations
“…Abbreviations: AhR, aryl hydrocarbon receptor; GALT, gutassociated lymphoid tissue; ILC, innate lymphoid cell; LTA, lipoteichoic acid; SIV, simian immunodeficiency virus; T h , T helper We and others have previously shown that CD3 2 CD8 high lymphocytes in the intestine represent a heterogeneous population including NK cells and other ILCs (2,23,24). In this study, we found that ILC3 subsets, defined by c-Kit + IL-7a + lineage-negative cells, are distinct from CD3 2 CD8 high cells, as indicated by ILC3 containing considerable CD3 2 CD8 2 cells (;70%) in macaques.…”
mentioning
confidence: 99%